Recurrent Pregnancy Loss and Associated Risk Factors - Nosheen Bano, Ayesha Naeem, Hafsa Mubashir, Nazia Tufail, Sadia Shafiq, Fozia Shaikh (Pakistan Journal of Medical & Health Sciences, 2022)
Background: As documented by the histopathology the recurrent pregnancy loss (RPL) is characterized as two or more miscarriages. The true prevalence of RPL is unknown, but is reported that two percent of women are affected by RPL per annum. A well-known risk factor for recurrent pregnancy losses is the high maternal age. Objective: This study was carried out to determine the risk factors and consequences of recurrent pregnancy loss. Study design: It is a prospective study Place and Duration: Conducted for the duration of one year from August 2021 to July 2022. The patients attended the obstetrician and gynecology department of Khawaja Muhammad Safdar Medical College, Allama Iqbal Memorial Teaching Hospital Sialkot. Material and Methods: This study was performed on 130 patients, admitted to tertiary care unit within the duration of one year. The written consent was taken from all the patients included in the study. The ethical and review board committee of the hospital approved the study. The women that had less than 2 miscarriages were excluded from the study. Results: The mean age of the mother at the time of admittance to hospital was 34 years and the mean of the miscarriages reported earlier in these patients were 2.9±1.3. The risk factors were found to be linked in most of the patients. The abnormality of the uterus and the thyroid dysfunction were some of the major risk factor in most of the patients with recurrent pregnancy loss. In case of thyroid dysfunction, the hyperthyroidism and hypothyroidism were studied and the results showed that the hyperthyroidism was present in case of 17% of the patients while hypothyroidism was found in 83% of the cases. Parental karyotype abnormality was also found in 4% of the cases. Conclusion: It was concluded that the patients suffering from recurrent pregnancy loss should underwent through the process of appropriate examination to clarify and conclude the risk factors involved in causing RPL. The protein S and factor XII deficiency may be playing a role in causing RPL, therefore LDA therapy can improve the rate of live birth in these patients. Keywords: recurrent pregnancy loss and protein S deficiency.